Affordance Feature Reasoning in Some Home Appliances Products - Lim, J. S.; Kim, Y. S. (Cranfield University Press, 2009)
Interactions between human and objects are made through specific features of the object, which are adequate to the task context. During interactions, the perceived features vary according to the context. Affordances are the messages that products provide and users perceive in such a way that user actions are naturally induced with the help of such messages. In this research, we define affordance features as structural elements providing affordances. We classify affordance features into functional, ergonomics, and informative aspects. For some home appliances, common affordances and affordance features are identified so that they can be used in designing other products.
Organised by: Cranfield University
Keywords: Affordances; Affordance Features; Task Context; Home Appliances Products